1999
DOI: 10.1262/jrd.45.167
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Porcine Delipated Oocytes and Embryos after Cryopreservation by Freezing or Vitrification.

Abstract: Abstract. The present study examined whether delipated porcine oocytes and embryos at various stages of development can be cryopreserved by conventional slow cooling or vitrification. Most (93%) of the 27 delipated morulae developed to blastocysts after freezing with 1.5 M propanediol + 0.1 M sucrose. Late morulae and early blastocysts delipated at 2-4 cell stage and cultured in vitro survived freezing either with 1.5 M glycerol + 0.25 M sucrose (10/18, 56%) or 1.8 M ethylene glycol + 0.25 M sucrose (14/19, 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 41 publications
(55 reference statements)
3
30
0
4
Order By: Relevance
“…Partial removal of lipid from porcine embryos (Nagashima et al 1995) and oocytes (Nagashima et al 1999) also reduces sensitivity to chilling and improves development after vitrification. There are abundant cytoplasmic lipids in porcine oocytes, and the amount of triglyceride, the main component of the lipids, is threefold higher than that in cattle and sheep oocytes (McEvoy et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial removal of lipid from porcine embryos (Nagashima et al 1995) and oocytes (Nagashima et al 1999) also reduces sensitivity to chilling and improves development after vitrification. There are abundant cytoplasmic lipids in porcine oocytes, and the amount of triglyceride, the main component of the lipids, is threefold higher than that in cattle and sheep oocytes (McEvoy et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The maturation of vitrified immature porcine oocytes can be improved (from 3.7% to 15.0%) by partial removal of cytoplasmic lipids (Park et al 2005). The effect of delipidization on oocyte vitrification has been reported (Nagashima et al 1999), and it was found that about 56% of the oocytes vitrified after delipidization survived, and 6% of oocytes could develop to morula stage after fertilization by subzonal sperm injection.…”
Section: Discussionmentioning
confidence: 99%
“…Our results on bovine embryos coincide with the ones reported in the pig by Nagashima et al (27), who found significantly improved in vitro survival rates after freezing delipidated embryos. The same group reported successful vitrification of pig embryos after delipidation (24,28). With bovine IVP embryos, Pangestu et al (30) did not obtain survival of delipidated blastocysts after slow freezing.…”
Section: Discussionmentioning
confidence: 99%
“…Nagashima and colleagues showed that the freezing tolerance of porcine oocytes [11] and early-stage embryos [12,13] can be dramatically increased by removing their cytoplasmic lipid droplets using a process called delipation.…”
mentioning
confidence: 99%